Cellular cofactors of HIV integrase: from target identification to discovery of ledgins - Debyser, Zeger (Henry Stewart Talks, 2011)
Cellular cofactors of HIV as novel antiviral targets, LEDGF/p75 is a tethering factor of HIV integrase, Identification of LEDGF/p75 as binding partner of integrase, Characterization of the interaction, Validation of integrase, LEDGF/p75 interaction as antiviral target, Assay and Drug Development, Transportin, SR2 is a nuclear import factor
Updated at 2021/03/03